Factors contributing to the performance of manufacturing firms in Pakistan - Waris Ali Khan (2020)
In these days rapidly evolving business marketplace, innovation has been considered as one of the most important factors for the success of firms. The Pakistani manufacturing industry has become an important component of the country's economic development. Unfortunately, the growth/performance of Pakistan's manufacturing industry is very low and facing difficulties to survive. Therefore, the foremost goal of this research is to study the effect of innovation (product and process innovation) as a mediator on the association between strategic orientation, entrepreneurial orientation, organizational culture and performance of manufacturing firms in Pakistan. This research was significantly encouraged by the inconsistent results and the gaps indicated in the contemporary literature regarding those relationships and have not been investigated together within the context of large manufacturing firms in Pakistan. This study adopted the Resource-Based View as an underpinning theory for its assumptions and to develop its model. Moreover, 399 self-administered questionnaires were distributed to large manufacturing firms in Pakistan. This research employed the partial least squares structural equation modeling to establish the validity and reliability of the measurement model and to test the relationships. The outcomes of this research showed that both strategic orientation and organizational culture have significant influences on performance of large manufacturing firms. However, entrepreneurial orientation found to have no direct effect on performance of large manufacturing firms. Furthermore, strategic orientation, entrepreneurial orientation and organizational culture have significant influences on innovation. More importantly, the results have also confirmed the mediating influence of innovation on the relationships between strategic orientation, entrepreneurial orientation, organizational culture and performance of large manufacturing firms. This study offers theoretical and practical contributions to academics and professionals. The limitations of the study have been addressed and some valuable recommendations for future research work are offered.